Severe clinical toxicity associated with analytically confirmed recreational use of 25I–NBOMe: case series. (July 2013) - Hill, Simon L.; Doris, Tom; Gurung, Shiv; Katebe, Stephen; Lomas, Alexander; Dunn, Mick; Blain, Peter; Thomas, Simon H. L.
Abstract Context. 4-Iodo-2, 5-dimethoxy-N-(2-methoxybenzyl)phenethylamine (25I-NBOMe) is a N-methoxybenzyl-substituted phenethylamine with potent serotoninergic effects. We describe seven cases of analytically confirmed toxicity due to the recreational use of 25I-NBOMe in the United Kingdom. Case series. Seven patients, all young adult males, presented to hospitals in the northeast of England with clinical toxicity after recreational drug use in January 2013. Clinical features included tachycardia (n = 7), hypertension (4), agitation (6), aggression, visual and auditory hallucinations (6), seizures (3), hyperpyrexia (3), clonus (2), elevated white cell count (2), elevated creatine kinase (7), metabolic acidosis (3), and acute kidney injury (1). LC–MS/MS analysis identified 25I-NBOMe as the main active substance in the plasma of all seven cases. Conclusions. Severe clinical toxicity may occur following recreational use of 25I-NBOMe, with stimulant and serotoninergic features predominating. Clinicians should be alert to this substance, in view of its emergence in Europe as well as in the United States.